Antiphospholipid-Related Chorea - Peluso, Silvio; Antenora, Antonella; De Rosa, Anna; Roca, Alessandro; Maddaluno, Gennaro; Brescia Morra, Vincenzo; De Michele, Giuseppe (Frontiers in Neurology, 2012)
Chorea is a movement disorder which may be associated with immunologic diseases, in particular in the presence of antiphospholipid antibodies (aPL). Choreic movements have been linked to the isolated presence of plasmatic aPL, or to primary or secondary antiphospholipid syndrome. The highest incidence of aPL-related chorea is detected in children and females. The presentation of chorea is usually subacute and the course monophasic. Choreic movements can be focal, unilateral, or generalized. High plasmatic titers of aPL in a choreic patient can suggest the diagnosis of aPL related-chorea; neuroimaging investigation does not provide much additional diagnostic information. The most relevant target of aPL is β2-glycoprotein I, probably responsible for the thrombotic manifestations of antiphospholipid syndrome. Etiology of the movement disorder is not well understood but a neurotoxic effect of aPL has been hypothesized, leading to impaired basal ganglia cell function and development of neuroinflammation. Patients affected by aPL-related chorea have an increased risk of thrombosis and should receive antiplatelet or anticoagulant treatment.